2012
DOI: 10.5142/jgr.2012.36.4.403
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Administration of Korea Red Ginseng Extract Increases Non-Rapid Eye Movement Sleep via GABAAergic Systems

Abstract: The current inquiry was conducted to assess the change in sleep architecture after long periods of administration to determine whether ginseng can be used in the therapy of sleeplessness. Following post-surgical recovery, red ginseng extract (RGE, 200 mg/ kg) was orally administrated to rats for 9 d. Data were gathered on the 1st, 5th, and 9th day, and an electroencephalogram was recorded 24 h after RGE administration. Polygraphic signs of unobstructed sleep-wake activities were simultaneously recorded with sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 29 publications
0
4
1
Order By: Relevance
“…Together, these findings indicate that Vietnamese ginseng does not have sedative–hypnotic effect. In contrast to the present result, a study by Lee et al [32] showed that repeated KRGE administration improves the sleep condition of rats. This discrepancy may be related to the various methodological differences between our studies (e.g., difference in doses, animal species, treatment scheme, and others).…”
Section: Resultscontrasting
confidence: 99%
“…Together, these findings indicate that Vietnamese ginseng does not have sedative–hypnotic effect. In contrast to the present result, a study by Lee et al [32] showed that repeated KRGE administration improves the sleep condition of rats. This discrepancy may be related to the various methodological differences between our studies (e.g., difference in doses, animal species, treatment scheme, and others).…”
Section: Resultscontrasting
confidence: 99%
“…Enomoto et al reported that the compounds isolated from Venenum Bufonis have inhibitory effects on IL-6 [15]. Lee and colleagues demonstrated various therapeutic effects of Ginseng and Ginseng extract [1618]. Ginsenoside is extract of Panax Ginseng.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported that marine organisms are useful as a functional food source that includes essential bioactive compounds, such as protein, essential fatty acids, vitamins and minerals, neuroactive compounds of catecholamine ( Athukorala et al ., 2006 , Lee et al , 2010 ). Ginseng or ginseng or ginsenosides isolated from ginseng extract have shown to have high affinity to GABA A ( Kimura et al , 1994 ) and 5-HT 2C receptors ( Cho et al ., 2010 ) and also have reported to increase non-rapid eye movement sleep ( Lee et al , 2012 ). Therefore, it has been suggested that GABA-enriched foods may have beneficial effects on sleep behaviors.…”
Section: Discussionmentioning
confidence: 98%